Analysis of the Impact of Labor on Seaweed Farming Income in Ghone Bhalano Village, Duruka District, Muna Regency - Saputra, Ilan; Yunus, Lukman; Zani, Munirwan (International Journal of Technology and Education Research, 2026)
This study aims to: 1) Determine the number of seaweed farming labor hours in Ghone Bhalano Village, 2) Determine the total income from seaweed farming in Ghone Bhalano Village, and 3) Analyze the influence of labor on seaweed farming income in Ghone Bhalano Village. This research was conducted from May to June in Ghone Bhalano Village, Duruka District, Muna Regency. The research location was determined purposively. The sample in this study consisted of 34 farmers and was determined using the census method. Data analysis used HKP analysis, simple linear regression analysis, and income analysis. The results showed that labor had a real and significant effect on income. The average income of seaweed farmers during one growing season is IDR 1,799,448